Effects of C content on the microstructure and properties of CoCrFeNiTi0.5Mo0.5Cx high-entropy alloy coatings by laser cladding - Tianxiang Lin; Meiyan Feng; Guofu Lian; Hua Lu; Changrong Chen; Xu Huang (Journal of Materials Research and Technology)
In order to deeply investigate the influence mechanism of different contents of non-metallic element C on the microstructure, microhardness, wear resistance and corrosion resistance of high-entropy alloy coatings. CoCrFeNiTi0.5Mo0.5Cx high-entropy alloy coating was prepared on the surface of AISI 1045 steel by laser cladding technology. The results show that the microstructure of CoCrFeNiTi0.5Mo0.5 without C addition consists of FCC phase, BCC phase, intermetallic compound phase and σ-phase structure, and the carbide phases (M7C3 and TiC) start to appear after the addition of C element. The microhardness of the coating increases and then decreases with the increase of C content, and the average hardness is the highest when x = 0.03, 495.3HV0.5, which is 27.6% higher than that of C0. The abrasion resistance of the CoCrFeNiTi0.5Mo0.5Cx high-entropy alloy coatings is gradually increased and then decreased with the increase of C content, and the wear amount decreases from 0.0813 mm3 to 0.0514 mm3, and the main frictional wear mechanisms are adhesive wear, abrasive wear and oxidative wear. With the increase of C content, the corrosion resistance of the coating is gradually improved and then reduced, when the C content is 0.03, the highest corrosion potential is −0.818V, the lowest corrosion current is 1.382E-4 A/cm2, at this time, the passivation film on the surface of the coating is the most stable and dense, with the best corrosion resistance. The results of this paper provide a theoretical reference for the effect of adding non-metallic elements on the microstructure and properties of high-entropy alloy coatings.